The feasibility and acceptability of a preventive intervention programme for children with depressed parents: study protocol for a randomised controlled trial. Issue 1 (December 2016) - de Angel, Valeria; Prieto, Fernanda; Gladstone, Tracy; Beardslee, William; Irarrázaval, Matías
Abstract Background One of the most important risk factors for childhood depression is being the child of a depressed parent. These at-risk children have two to four times the probability of having an affective episode compared with their peers. Preventive interventions such as Beardslee's Preventive Intervention Program (PIP) that are targeted at children of depressed parents have proven effective in many countries. The PIP is a family-based approach that works by promoting resilience in children and increasing positive interactions within the family. In this pilot randomised controlled trial (RCT), we will determine the acceptability and feasibility of an adapted version of this intervention in Chile. Methods/design We are conducting a pilot RCT with a manualized intervention. The intervention will be delivered in seven weekly sessions at the family home. It is targeted mostly at parents but will also measure outcomes among the children. Control subjects will follow their treatment as usual. Feasibility and acceptability will be assessed by recruitment, adherence, dropout and level of missing data, as well as the burden of scales and measurement tools. Families will be followed for 11 months. Discussion Given the negative lifelong consequences of depression and the burden they represent, preventive programmes are not only feasible but necessary. Despite the successful implementation of this intervention in different countries, an adaptation to the Chilean reality will be prerequisite. The results of this pilot study will inform a definitive trial that will make the case for its national implementation. Trial registration Clinicaltrials.gov trial identifier:NCT02593266 . Registration date: 30 Octo 2015.